A experiência de filho(a) enlutado(a) de pais que deram fim à própria vida. - Cavalcante Filho, Pedro Pereira (2024)
The end of life emerges as a possibility of the human being from Antiquity to contemporaneity. In the face of such an event, mourning, as a response of human existence to the loss of a loved one, is also present, as a phenomenon, in the same period of time to which it was alluded to. The general objective of this work is to understand the experience of the bereaved child of parents who have ended their own life, and the specific objectives are: a) to briefly problematize the phenomenon of ending life and mourning in the West; b) describe the way "how" the grief of children whose father or mother ended their own life is being experienced; and c) to explain the comprehensive possibilities of the way in which the "hermeneutic situation" is presented in the narrative of the collaborators, in attention to the hermeneutic circularity, which points to the dimension of meaning. The research is of a phenomenological qualitative nature, illuminated by the assumptions of Martin Heidegger's Hermeneutic Phenomenology, especially those that deal with the hermeneutic situation and its coordinates – point of view, perspective and horizon. We interviewed five children, four females and one male. The methodical path was followed from the narratives of the collaborators and the diary of affectations of this researcher, to understand how each one experienced the loss of their loved one. In dialogue with the collaborators, the starting point was the search for explanations to justify the pain and suffering for the loss of the father/mother. The narratives draw attention for revealing the struggle faced by collaborators of the research to redirect their lives. In their singularities, they experienced fear, despair, sadness, anxiety, disorientation, helplessness, anger, guilt, memory loss, abandonment, judgments and prejudices. Professing a spiritual belief made it possible to elaborate the experience of grief with less grief for the loss. The support network, when present with the collaborators, was fundamental for the reception of suffering. We noticed that the stigma and taboo surrounding the end of life reinforce, in society, previous concepts, which can link the act to the profession of psychologist, as if this professional had the power to prevent the death of the person who decided to give up on life. We also observed that the media can amplify the event and generate, in society, popular commotion, making it difficult to carry out funeral acts, as occurred with one of the collaborators.